2020
DOI: 10.1029/2019ja027314
|View full text |Cite
|
Sign up to set email alerts
|

Proton Acceleration by Io's Alfvénic Interaction

Abstract: The Jovian Auroral Distributions Experiment aboard Juno observed accelerated proton populations connected to Io's footprint tail aurora. While accelerated electron populations have been previously linked with Io's auroral footprint tail aurora, we present new evidence for proton acceleration due to Io's Alfvénic interaction with Jupiter's magnetosphere. Separate populations were accelerated above the Io torus and at high latitudes near Jupiter. The timing suggests the acceleration is due to Alfvén waves associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 59 publications
4
38
0
Order By: Relevance
“…Without comparing to coincident magnetic field data, we cannot conclusively determine whether these signatures are Alfvénically accelerated versus another broadband acceleration mechanism. Yet, given the success of the Alfvén wave back‐tracing and that the distributions are not consistent with static downward inverted‐V acceleration, such distributions fit within the body of increasing evidence for Alfvénic acceleration sustaining tail emissions in the Juno era (Bonfond, Saur, et al, 2017; Damiano et al, 2019; Gershman et al, 2019; Saur et al, 2018; Sulaiman et al, 2020; Szalay, Bagenal, et al, 2020; Szalay et al, 2018). We mention that during the PJ12N transit, Poynting fluxes associated with the turbulent cascade of low‐frequency transverse fluctuations in the magnetic field indicative of Alfvénic fluctuations were estimated to be ~3,000 mW/m 2 (Gershman et al, 2019).…”
Section: Discussionmentioning
confidence: 62%
“…Without comparing to coincident magnetic field data, we cannot conclusively determine whether these signatures are Alfvénically accelerated versus another broadband acceleration mechanism. Yet, given the success of the Alfvén wave back‐tracing and that the distributions are not consistent with static downward inverted‐V acceleration, such distributions fit within the body of increasing evidence for Alfvénic acceleration sustaining tail emissions in the Juno era (Bonfond, Saur, et al, 2017; Damiano et al, 2019; Gershman et al, 2019; Saur et al, 2018; Sulaiman et al, 2020; Szalay, Bagenal, et al, 2020; Szalay et al, 2018). We mention that during the PJ12N transit, Poynting fluxes associated with the turbulent cascade of low‐frequency transverse fluctuations in the magnetic field indicative of Alfvénic fluctuations were estimated to be ~3,000 mW/m 2 (Gershman et al, 2019).…”
Section: Discussionmentioning
confidence: 62%
“…These auroral emissions (Figure 5c) indicate that the plasma‐satellite interactions all involve electrodynamic perturbations, which generate Alfvén waves propagating from the moon, carrying electric currents parallel to the magnetic field, accelerating electrons that bombard Jupiter's atmosphere and generate auroral emissions. The Juno mission is revealing new details about these auroral emissions and flying through the polar end of the fluxtubes that couple to the moons (Hue et al, 2019; Mura et al, 2018; Paranicas et al, 2019; Szalay et al, 2018, 2019).…”
Section: Plasma‐satellite Interactionsmentioning
confidence: 99%
“…Analyses of the Io UV footprint morphology indicated that the electron acceleration leading to the aurora should be both bidirectional and broadband (Bonfond et al, 2008, 2009), and subsequent theoretical modeling by Hess et al (2010) demonstrated that such acceleration occurs at high latitudes by a turbulent cascade of Alfvén waves. Moreover, broadband energy distributions found in the Io footprint tail (Szalay et al, 2018, 2019) suggested continued Alfvénic interaction downstream of Io (Bonfond et al, 2017; Jacobsen et al, 2010; Mura et al, 2018). Similar distributions in Ganymede's footprint tail further reinforce the conclusion that Alfvénic interactions sustain satellite‐magnetosphere coupling well into the downstream region (Szalay, Allegrini, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%